2011
DOI: 10.1039/c1cp20166b
|View full text |Cite
|
Sign up to set email alerts
|

The electro-oxidation of formate ions at a polycrystalline Pt electrode in alkaline solution: an in situ FTIR study

Abstract: This paper reports in situ FTIR studies on the oxidation of formate at polycrystalline Pt in aqueous KOH. Data are presented which show that hydroxyl species play a major role in the electro-oxidation of small organic molecules under alkaline conditions at polycrystalline Pt, and that a number of possible mechanistic pathways are possible. Small changes in experimental conditions appear to be able to cause the reaction to flick between these pathways; for example, the presence of oxygen has a marked effect upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 48 publications
7
37
0
Order By: Relevance
“…14 In line with other experimental studies, [15][16][17]10,11,7,18,19 we found that a 5 potential improvement in the selectivity lies in the competition between two routes represented schematically in Figure 1.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…14 In line with other experimental studies, [15][16][17]10,11,7,18,19 we found that a 5 potential improvement in the selectivity lies in the competition between two routes represented schematically in Figure 1.…”
Section: Introductionsupporting
confidence: 78%
“…9 Christensen et al have shown that the interfacial pH drops at higher potentials due to the high consumption of OH -which is not completely counterbalanced by the OH -diffusion from the bulk-phase. [10][11][12] This phenomenon leads to a transition from alkaline to acidic conditions at the interphase. The transition potential varies with the diffusion rate of OH -which is dependent on the temperature and mass flow-rate.…”
Section: Introductionmentioning
confidence: 99%
“…This poor selectivity for ethanol oxidation to carbonate at Pt has been attributed to [8] the adsorption of the ethanol molecule via the O atom on the C 1 carbon; the removal of the first two electrons from the adsorbate then generates acetaldehyde, CH 3 CHO, which is able to desorb (see scheme 1) as such, but can also itself be oxidised in a second two-electron step to acetate, which in turn can be displaced from the surface by the ethanol in solution. Work in Newcastle on methanol [9], formate [10] and ethanol [11] oxidation supports this postulate in terms of oxidation in alkaline media, with clear evidence of adsorption through O rather than through C, and with evidence that it is adsorption through the the latter of which is necessary for C-C cleavage.…”
Section: Introductionmentioning
confidence: 86%
“…3(a) show: the growth of water gain features near 3335 cm À1 and 1647 cm À1 , the loss of OH À (broad bands near 2700 and 1875 cm À1 ref. [9][10][11], the gain of a band due to bridgebonded CO (CO B ) at 1862 cm À1 , 19,20 the gain of a band near 1395 cm À1 with a small gain feature at ca. 1300 cm À1 .…”
Section: Infrared Datamentioning
confidence: 99%
“…[43]; this value varies very little between 14 ºC and 45 ºC[44]. The substantial drop in pH in thin-layer FTIR spectroscopic experiments has been modelled in terms of the slow diffusion of OHions across the electrode surface coupled with the exhaustion of reactant[31][32].…”
mentioning
confidence: 99%